Features of forecasting abnormally high reservoir pressures when drilling wells in areas of south-western Turkmenistan - Deryaev, Annaguly (Innovaciencia, 2023)
Introduction: The study is essential because predicting areas with high formation pressures in geophysical research is complex. It requires new technologies to accurately locate them and minimize unforeseen emergencies. The purpose of this study is to analyse and identify the peculiarities of predicting anomalously high formation pressures during well drilling in the territory of south-western Turkmenistan in order to provide more effective and reliable pressure management during drilling and operation. Materials and Methods: Methods such as analysis and prediction were used in this study. Results and Discussion: The paper presents valuable research data highlighting the changes in reservoir pressure gradients in the unique stratigraphic section of reservoirs in the oil and gas fields of the Pribalkan and Gogerendag-Ekerem zones. The analysis of the studies reveals the dynamism with which the properties of reservoir rock change with increasing depth of occurrence. Special attention is paid to the processes associated with the formation of anomalously high formation pressures, which is an important aspect for understanding complex geological processes. Conclusions: The study provides a detailed classification of formation pressures, considering the anomaly coefficient, enhancing our understanding of this phenomenon. Predicting formation pressures for specific horizons relies on analyzing deep well drilling results.
Keywords: Miocene; enhanced oil recovery; adjacent territories; drilling fluid; hydrodynamics